The Effect of Technology-Enhanced Classrooms in Middle School Education - Eyyam, Ramadan (Igi Global, 2017)
This study examined whether technology-enhanced classrooms enhanced students' learning despite their various dominant intelligences and learning styles. For this purpose, a comprehensive investigation was used to verify whether and in what ways students benefit from technology-enhanced classrooms. As the research design, a cross-implementation experimental method was developed for the study by the researcher. Lesson plans and materials were prepared for English and mathematics subjects considering Gagne's nine events of instruction and Bloom's taxonomy. The Technology-enhanced Classroom Perception Scale and a standardized open-ended interview were prepared to examine the perceptions of both students and teachers. In the end, some interesting differences were found between the treatment and control groups, although they were not significant. One of the most important reasons for this might be the positive attitudes of English teachers in general but negative attitudes of mathematics teachers towards technology-enhanced classroom.
Keywords: Performance